Gun Ownership Legality and Its Power in American Society - Jones, Dennis Ivan (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
This research is under a descriptive qualitative method. Therefore, library research was used to compile primary data. The primary data was taken from the documentary film, and the secondary data was taken from sources such as books, articles, and journals. Method of American studies or interdiciplinary approach was also apllied with theories to analyze the problem formulation in this research. They were American politics towards gun laws, sociological theory, and popular culture. The result shows that American policy towards gun legality  is less tight and it give many bad impacts to  American society. The rules that have been made by the American government still  considered  weak and make American justify any illegal way to get their own gun easily. Therefore, the American government is supposed to improve the laws of gun ownership legality to decrease the impacts of gun problems.